Pembuatan Game Edukasi Pintar Memilah Sampah Berbasis Android - Putra, Rizki Catur; , Dedi Gunawan, S.T., M.Sc (2016)
Garbage is unwanted residual material after the end of a process, and is closely related to public health. Inside the garbage will live a wide variety of pathogenic microorganisms, insects and animals also transfer / spreading disease. Trash still give rise to problems which are difficult to control. This problem occurs because of a lack of concern for everyone to dispose of waste in place. The waste bins for education should be given as early as possible to children, so that children are increasingly concerned about the environment. Education dispose of waste should be interesting. Internet has many games about taking out the trash, but from the look and the gameplay is still lacking attract children to play. With the above problems, the researchers aim to design and create a game application to learn while playing. Making educational game using several methods, the method of determining the type of categorization of garbage, and the determination of the object used in the introduction of this kind of garbage. Making this application begins with making a storyboard of the game, then the assets supporting educational game apps using Construct 2 as a building game, Corel Draw to create objects, and Voice Recorder to record sounds. The results of this analysis, an application edugame introduction of waste sorting according to category. Based on the test black box, it can be concluded that this edugame can work well.